3х-1=2(х-2) 2)3(х+5)=7-5х 3) 19(у-9)=3(у+7) 4)4(х-9)=3(х-8) 5)3(2х-9)=5(х-4) 6) 7(3-2х)=15(1-х)

Коши Коши    1   21.08.2019 22:30    0

Ответы
tolikking05 tolikking05  05.10.2020 10:16
3х-1=2(х-2)      3(х+5)=7-5х           19(у-9)=3(у+7)        
3х-1=2х-4         3х+15=7-5х           19у-171=3у+21
3х-2х=-4+1       3х+5х=7-15           19у-3у=21+171
х=-3                   8х=-8                     17у=192
                          х=-1                       у=11,3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика